Digital literacy among students: a case study at centre of foundation study in management / Prof. Dr. Zahayu Md Yusof ... [et al.] - Md Yusof, Zahayu; Lim, Qing Jun; Goh, Hong Quan; Sobri, Anis Hanisah; Mahmud, Nur Athirah (Universiti Teknologi MARA, Kedah, 2023)
Digital literacy is the ability to navigate the digital world using reading, writing, technical skills, and critical thinking, together with the ability to discover, evaluate, utilize, share, and create content using information technologies. Access to the Internet has increased from time to time. The percentage of households accessing smartphones had grown from previous years. It showed that technology has seeped into our daily life and encouraged more processes to become data driven and virtual. This study will use descriptive statistical methods to determine the digital literacy level among Foundation Studies in Management students and to identify reasons the students engage in digital technologies. The findings show that female students tend to spend more hours on their cell phones and computers. In addition, most of the Foundation Studies in Management students responded to a moderate-high agreement on their level of digital literacy, which means that most of them understand and can apply simple and fundamental computer knowledge for personal purposes and academic matters.